Low-viscosity silicon carbide ceramic slurry as well as preparation method and application thereof
By modifying the combined dispersant of α-SiC powder with tetramethylammonium hydroxide and octadecamine polyoxyethylene ether, the problem of poor stability of high solid content and low viscosity slurry in the production of silicon carbide ceramic components is solved, and the stability of slurry in the production of silicon carbide ceramic components is achieved. Preparation of silicon carbide ceramic slurry with high solid content, low viscosity and good stability, suitable for grouting and forming.
Patent Information
- Application Number
- CN202411318621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-20
AI Technical Summary
In the production of silicon carbide ceramic components, it is difficult to prepare slurries with high solid content, low viscosity and stable performance, resulting in powder aggregation and settlement during grouting and forming.
Modified α-SiC powder, tetramethylammonium hydroxide and octadecamine polyoxyethylene ether as dispersants, and a high solids content and low viscosity silicon carbide ceramic slurry is formed by modification treatment and stirring. Using Al(NO3)3 and sodium humate to modify α-SiC powder, tetramethylammonium hydroxide provides a strong alkaline environment, octamine polyoxyethylene ether forms hydrogen bonds or van der Waals adsorbs it on the surface of the powder. Prevent aggregation and precipitation.
A silicon carbide ceramic slurry with a solid content of 50vol.% was obtained, with a viscosity of 0.1123Pa·s to 0.5633Pa·s, and a settlement height of 2mm to 5mm after 24 hours was left to stand for 24 hours. It has good stability, conforms to high solids content and is low. Viscosity requirements.
Smart Images

Figure BDA0005052947650000061 
Figure BDA0005052947650000101 
Figure BDA0005052947650000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a low-viscosity silicon carbide ceramic slurry and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Silicon carbide ceramic material is a new type of high-temperature resistant ceramic with extremely strong covalent bonds. It has been widely used in the field of high-tech in recent years. It can be used as high-temperature furnaces, rocket combustion chamber linings, radar antenna covers, precision bearings, ceramic engines, nozzles, high-temperature turbine rotors, fuel devices, heat exchange components, nuclear reactor materials, etc.
[0004] The high reliability of silicon carbide materials is inseparable from its molding process. The molding process of silicon carbide ceramic materials is mainly divided into wet molding and dry molding. Dry molding includes dry pressing molding and isostatic pressing molding. Wet molding includes plastic forming type and colloidal molding. Colloidal molding mainly includes slip casting molding, tape casting and new colloidal molding methods.
[0005] Slip casting is a near-net-shape forming technology method with a relatively simple forming process, easy-to-control process, high efficiency, low cost, good uniformity of formed silicon carbide ceramic blanks, and can form complex geometric shapes, large sizes, porous tubular supports and thin-walled blanks. The slip casting forming process of silicon carbide ceramics is as follows: inject an appropriate amount of water-soluble ceramic powder organic suspension slurry with good dispersibility into the gypsum mold, use the capillary force of the small holes in the gypsum mold to absorb excess water in the slurry, solidify the slurry, and adhere to the inner wall of the gypsum mold. After a certain period of drying and shrinkage, the formed blank is gradually separated from the gypsum mold, and the blank is removed from the mold.
[0006] The success of grouting molding depends on the preparation of slurry, which is a crucial step. The required slurry has high solid content (volume solid content ≥ 50%), low viscosity (≤ l Pa·S), good fluidity, good stability, high uniformity, low thixotropy, and good permeability. Low viscosity facilitates smooth grouting, while high solid content ensures the acquisition of high-density and high-strength green blanks. However, there is a certain contradiction between high solid content and low viscosity. The high solid content powder will produce a certain amount of agglomeration and sedimentation. Therefore, how to prepare high solid content, low viscosity, and stable performance silicon carbide ceramic slurry has become an urgent problem to be solved in the field of silicon carbide ceramic component production. Summary of the invention
[0007] In order to overcome the above problems, the present invention provides a low-viscosity silicon carbide ceramic slurry and a preparation method and application thereof.
[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0009] A first aspect of the present invention provides a low-viscosity silicon carbide ceramic slurry, the components of which include: modified α-SiC powder and a dispersant, wherein the dispersant is tetramethylammonium hydroxide.
[0010] The second aspect of the present invention provides a method for preparing the silicon carbide ceramic slurry according to the first aspect, comprising:
[0011] Mixing tetramethylammonium hydroxide and deionized water to obtain a mixed dispersion;
[0012] The modified α-SiC powder is added into the mixed dispersion in batches, and stirred to obtain silicon carbide ceramic slurry.
[0013] The beneficial effects of the present invention are:
[0014] (1) In order to improve the dispersion stability of α-SiC powder in water, Al(NO3)3 and sodium humate are first used to modify it. The α-SiC powder modified with Al(NO3)3 has better hydrophilicity, and the Zeta potential of the surface of the modified α-SiC powder is negative. Sodium humate forms hydrogen bonds or van der Waals forces with the surface of the α-SiC powder and is adsorbed on the surface of the α-SiC particles, forming a steric hindrance to prevent the powder from aggregating and precipitating. The modified α-SiC powder is dispersed in the mixed dispersion, and tetramethylammonium hydroxide will be ionized in water: The generated OH - Providing a strong alkaline environment for the solution greatly increases the amount of negative charge on the surface of the modified α-SiC powder, reduces the surface negative Zeta potential, and prevents the agglomeration of the α-SiC powder. When the dispersant includes octadecylamine polyoxyethylene ether, the hydroxyl groups in the octadecylamine polyoxyethylene ether molecules form hydrogen bonds or van der Waals forces with the surface of the α-SiC powder, thereby adsorbing on the surface of the α-SiC particles, forming a steric hindrance to prevent the powder from agglomerating and precipitating. Therefore, the present invention can obtain a silicon carbide ceramic slurry with high solid content, low viscosity, and stable performance.
[0015] (2) The silicon carbide ceramic slurry prepared by the present invention has a viscosity of 0.1123 Pa·s to 0.5633 Pa·s at a solid content of 50 vol.%, and a sedimentation height of 2 mm to 5 mm after standing for 24 hours, which has good stability and meets the requirements of high solid content and low viscosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0017] Figure 1 The viscosity test results of the silicon carbide ceramic slurry prepared in Examples 2 to 4;
[0018] Figure 2 These are the viscosity test results of the silicon carbide ceramic slurries prepared in Examples 5 to 8. DETAILED DESCRIPTION
[0019] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0020] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0021] A first typical embodiment of the present invention provides a low-viscosity silicon carbide ceramic slurry, the components of which include: modified α-SiC powder and a dispersant, wherein the dispersant is tetramethylammonium hydroxide.
[0022] In one or more embodiments, the mass ratio of the modified α-SiC powder to tetramethylammonium hydroxide is 100:1.5-2.5.
[0023] In one or more embodiments, the dispersant further comprises octadecylamine polyoxyethylene ether.
[0024] Preferably, the mass ratio of the modified α-SiC powder to tetramethylammonium hydroxide and octadecylamine polyoxyethylene ether is 100:1.5-2.5:0.3-1.0, preferably 100:2:0.3-1.0.
[0025] In one or more embodiments, the preparation method of the modified α-SiC powder includes: placing α-SiC powder and aluminum salt in deionized water, heating and stirring, then adding sodium humate (C9H8Na2O4), continuing to stir, and then collecting the solid to obtain the modified α-SiC powder.
[0026] Preferably, the particle size of the α-SiC powder is 0.5-5 μm, preferably 2.5 μm.
[0027] Preferably, the aluminum salt comprises Al(NO3)3.
[0028] Further preferably, the mass ratio of α-SiC powder to Al(NO3)3 is 1:0.003 to 0.007.
[0029] Preferably, the mass ratio of deionized water to α-SiC powder is 2:0.5-1.2, preferably 2:1.
[0030] Preferably, the heating and stirring temperature is 60 to 80° C., the heating and stirring time is 2.5 to 4.5 hours, and the stirring rate is 400 r / min to 600 r / min.
[0031] Preferably, the mass ratio of α-SiC powder to sodium humate is 1:0.004-0.009, preferably 1:0.008.
[0032] Preferably, the stirring time is continued for 2.5 to 4.5 hours.
[0033] Preferably, the method for collecting the solid comprises centrifuging and removing the supernatant to obtain the aluminum salt-modified α-SiC powder.
[0034] More preferably, the centrifugal separation rate is 3500-4500 r / min, and the centrifugal separation time is 5-15 min.
[0035] Preferably, the solid is collected, dried, and then passed through a 80-100 mesh sieve to obtain the modified α-SiC powder.
[0036] The second aspect of the present invention provides a method for preparing the silicon carbide ceramic slurry according to the first aspect, comprising:
[0037] Mixing tetramethylammonium hydroxide and deionized water to obtain a mixed dispersion;
[0038] The modified α-SiC powder is added into the mixed dispersion in batches, and stirred to obtain silicon carbide ceramic slurry.
[0039] In one or more embodiments, tetramethylammonium hydroxide, octadecylamine polyoxyethylene ether and deionized water are mixed to obtain a mixed dispersion.
[0040] In one or more embodiments, tetramethylammonium hydroxide and deionized water are stirred and mixed to obtain a mixed dispersion, the stirring rate is 400 r / min to 600 r / min, and the stirring time is 10 min to 20 min.
[0041] In one or more embodiments, during the process of stirring to obtain the silicon carbide ceramic slurry, the stirring rate is 400 r / min to 600 r / min, and the stirring time is 16 h to 24 h.
[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0043] Example 1
[0044] Preparation of modified α-SiC powder:
[0045] Disperse 100g of α-SiC powder with a purity of 99.5% and a particle size of 2.5μm and 0.5g of Al(NO3)3 powder with a purity of 99.5% in 200mL of deionized water, place the entire system in a 70°C water bath, stir and react at a rate of 500r / min for 3h; then continue to add 0.8g of sodium humate to the reaction system and continue stirring for 3h. Centrifuge the stirred α-SiC suspension through a high-speed centrifuge (4500r / min, 10min) to separate the supernatant, collect the solid, place it in a blast drying oven at 70°C and dry it through an 80-100 mesh sieve to obtain the modified α-SiC powder.
[0046] Example 2
[0047] 0.96 g of 25% aqueous solution of tetramethylammonium hydroxide (0.24 g of tetramethylammonium hydroxide and 0.72 mL of water) and 4.04 mL of deionized water were added into a beaker, and stirred evenly with a mechanical stirrer at a speed of 500 r / min for 15 min to obtain a mixed dispersion.
[0048] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0049] Solid content calculation formula:
[0050]
[0051] Example 3
[0052] 1.28 g of 25% aqueous solution of tetramethylammonium hydroxide (0.32 g of tetramethylammonium hydroxide and 0.96 mL of water) and 3.72 mL of deionized water were added into a beaker, and stirred evenly with a mechanical stirrer at a speed of 500 r / min for 15 min to obtain a mixed dispersion.
[0053] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0054] Example 4
[0055] 1.6 g of 25% aqueous solution of tetramethylammonium hydroxide (0.4 g of tetramethylammonium hydroxide and 1.2 mL of water) and 3.4 mL of deionized water were added into a beaker, and stirred evenly with a mechanical stirrer at a speed of 500 r / min for 15 min to obtain a mixed dispersion.
[0056] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0057] The viscosity test results of the silicon carbide ceramic slurry prepared in Examples 2 to 4 are as follows: Figure 1 shown.
[0058] from Figure 1 It can be seen that under different tetramethylammonium hydroxide addition amounts, the viscosity of the silicon carbide ceramic slurry with a solid content of 50 vol.% tends to decrease with increasing shear rate. When the tetramethylammonium hydroxide addition amount is 2.0 wt.%, the slurry viscosity is the lowest and the silicon carbide particle dispersion effect is the best.
[0059] Example 5
[0060] Add 1.28 g of 25% aqueous solution of tetramethylammonium hydroxide (0.32 g of tetramethylammonium hydroxide and 0.96 mL of water), 0.048 g of octadecylamine polyoxyethylene ether and 3.72 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 500 r / min, and stir for 15 min to obtain a mixed dispersion.
[0061] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0062] Example 6
[0063] Add 1.28 g of 25% aqueous solution of tetramethylammonium hydroxide (0.32 g of tetramethylammonium hydroxide and 0.96 mL of water), 0.09 g of octadecylamine polyoxyethylene ether and 3.72 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 500 r / min, and stir for 15 min to obtain a mixed dispersion.
[0064] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0065] Example 7
[0066] Add 1.28 g of 25% aqueous solution of tetramethylammonium hydroxide (0.32 g of tetramethylammonium hydroxide and 0.96 mL of water), 0.112 g of octadecylamine polyoxyethylene ether and 3.72 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 500 r / min, and stir for 15 min to obtain a mixed dispersion.
[0067] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0068] Example 8
[0069] Add 1.28 g of 25% aqueous solution of tetramethylammonium hydroxide (0.32 g of tetramethylammonium hydroxide and 0.96 mL of water), 0.16 g of octadecylamine polyoxyethylene ether and 3.72 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 500 r / min, and stir for 15 min to obtain a mixed dispersion.
[0070] 16g of the modified α-SiC powder prepared in Example 1 was added to the mixed dispersion in batches, with the added masses being 8g, 4g, 1g, 1g, and 1g, respectively, and finally the remaining 1g of powder was added in 10 times. At the same time, the speed of the magnetic stirrer was adjusted to 200r / min to 400r / min according to the viscosity and the operation was continued until all the modified α-SiC was added to the beaker to form a slurry; the slurry was continued to be stirred for 20h to obtain a silicon carbide ceramic slurry with a solid content of 50vol.%.
[0071] The viscosity test results of the silicon carbide ceramic slurries prepared in Examples 5 to 8 are as follows: Figure 2 shown.
[0072] from Figure 2 It can be seen that when the addition amount of tetramethylammonium hydroxide is 2.0wt.%, the viscosity of silicon carbide slurry with a solid content of 50vol.% tends to decrease with increasing shear rate at different addition amounts of octadecylamine polyoxyethylene ether. When the addition amount of octadecylamine polyoxyethylene ether is 0.7wt.%, the relative viscosity of the slurry is the lowest, and the dispersion effect of silicon carbide particles in the slurry is the best.
[0073] Comparative Example 1
[0074] When the addition amount of tetramethylammonium hydroxide is 0 wt.%, the maximum solid content of the ceramic slurry formed by the modified silicon carbide powder does not exceed 43 vol.%, and cannot reach the standard of 50 vol.% solid content.
[0075] Comparative Example 2
[0076] Change to another solvent.
[0077] Tetramethylammonium hydroxide cannot be replaced by ethanol, butanone, n-butanol, toluene, and ethyl acetate solvents. This is because tetramethylammonium hydroxide hydrolyzes in the slurry to produce hydroxyl groups, providing a strong alkaline environment. Another hydrolysis product is adsorbed on the surface of silicon carbide particles to increase the thickness of the double electron layer, which reduces the Zeta potential of silicon carbide particles and improves the dispersibility of the slurry. The hydroxyl groups in octadecylamine polyoxyethylene ether are adsorbed on the surface of silicon carbide particles through hydrogen bonds or van der Waals forces to form an adsorption layer that plays a steric hindrance role. It can be replaced by other substances that can be adsorbed on the surface of the powder, but the effects on the slurry are different.
[0078] Comparative Example 3
[0079] When the dispersant is only tetramethylammonium hydroxide and silicon carbide is not modified, the unmodified silicon carbide powder can form a silicon carbide ceramic slurry with a solid content of 50 vol.% under the dispersing action of 2 wt.% tetramethylammonium hydroxide. However, the viscosity of the slurry is 0.8428 Pa·s, which is much higher than the slurry prepared with modified silicon carbide. At the same time, the stability is 7.231, which is higher than 5.882 of the slurry prepared with modified silicon carbide. This shows that the modification of Al(NO3)3 and sodium humate can effectively improve the dispersibility and stability of silicon carbide ceramic slurry.
[0080] The components of the silicon carbide ceramic slurries prepared in Examples 2 to 8 and the test results of viscosity and stability are shown in Table 1.
[0081] Table 1 Composition of silicon carbide ceramic slurry and test results of viscosity and stability
[0082]
[0083]
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-viscosity silicon carbide ceramic slurry, characterized in that: The components of the silicon carbide ceramic slurry include: modified α-SiC powder and a dispersant, wherein the dispersant is tetramethylammonium hydroxide.
2. The silicon carbide ceramic slurry according to claim 1, characterized in that The mass ratio of the modified α-SiC powder to tetramethylammonium hydroxide is 100:1.5-2.
5.
3. The silicon carbide ceramic slurry according to claim 1, characterized in that: The dispersant also includes octadecylamine polyoxyethylene ether.
4. The silicon carbide ceramic slurry according to claim 3, characterized in that: The mass ratio of the modified α-SiC powder to tetramethylammonium hydroxide and octadecylamine polyoxyethylene ether is 100:1.5-2.5:0.3-1.0, preferably 100:2:0.3-1.
0.
5. The silicon carbide ceramic slurry according to claim 1, characterized in that The preparation method of the modified α-SiC powder includes: placing α-SiC powder and aluminum salt in deionized water, heating and stirring, then adding sodium humate, continuing to stir, and then collecting solid to obtain the modified α-SiC powder.
6. The silicon carbide ceramic slurry according to claim 5, characterized in that: The particle size of the α-SiC powder is 0.5 to 5 μm, preferably 2.5 μm; Or, the aluminum salt includes Al(NO3)3, preferably, the mass ratio of α-SiC powder to Al(NO3)3 is 1:0.003-0.007; Alternatively, the mass ratio of deionized water to α-SiC powder is 2:0.5-1.2, preferably 2:
1.
7. The silicon carbide ceramic slurry according to claim 5, characterized in that The heating and stirring temperature is 60-80°C, the heating and stirring time is 2.5-4.5h, and the stirring rate is 400r / min-600r / min; Or, the mass ratio of α-SiC powder to sodium humate is 1:0.004-0.009, preferably 1:0.008; Or, continue stirring for 2.5 to 4.5 hours; Or, the method for collecting the solid includes centrifugation to remove the supernatant to obtain aluminum salt-modified α-SiC powder; preferably, the centrifugal separation rate is 3500-4500 r / min, and the centrifugal separation time is 5-15 min; Alternatively, the solid is collected, dried, and then passed through a 80-100 mesh sieve to obtain modified α-SiC powder.
8. The method for preparing the silicon carbide ceramic slurry according to any one of claims 1 to 7, characterized in that: include: Mixing tetramethylammonium hydroxide and deionized water to obtain a mixed dispersion; The modified α-SiC powder is added into the mixed dispersion in batches, and stirred to obtain silicon carbide ceramic slurry.
9. The preparation method according to claim 8, characterized in that: Tetramethylammonium hydroxide, octadecylamine polyoxyethylene ether and deionized water are mixed to obtain a mixed dispersion.
10. The preparation method according to claim 8, characterized in that: Tetramethylammonium hydroxide and deionized water are stirred and mixed to obtain a mixed dispersion, the stirring rate is 400 r / min to 600 r / min, and the stirring time is 10 min to 20 min; Alternatively, during the process of stirring to obtain the silicon carbide ceramic slurry, the stirring rate is 400 r / min to 600 r / min, and the stirring time is 16 h to 24 h.
Citation Information
Patent Citations
Preparation method of silicon carbide slurry for injection molding
CN108298988A
Preparation method of silicon carbide micro powder
CN116854483A
Method for preparing high-thermal-conductivity and high-strength Si / SiC ceramic material through 3D printing
CN118184361A
Preparation method of high-strength and high-modulus reactive sintering silicon carbide material
CN118324533A
Preparation method of ceramic composite material 3D printing wire rod
CN118324534A
